Assessing and Improving the Quality and Reliability of Company X as a Supplier - Pessala, Lotta (My University, 2026)
Product quality, delivery reliability, and effective communication are critical factors in supplier performance, especially in B2B context. Supplier quality and reliability can be evaluated through customer satisfaction, which is why organizations should focus on maintaining and improving it. Customer satisfaction also leads to loyalty and long-term relationships between a customer and supplier. This study aimed to evaluate the performance of a case company operating in energy industry and to identify improvement areas to enhance customer satisfaction and operational efficiency. The study was conducted as a single case study using both qualitative and quantitative methods. Internal insights were gathered through semi-structured employee interviews while external customer perceptions were collected with questionnaire. The collected data was analysed through thematic and statistical analyses to find strengths and weaknesses as well as areas for improvement. The results of the research indicated that product quality is perceived as a strength at the case company, while delivery reliability and responsiveness to customers’ problems were identified as areas to be improved. Correlation tests showed that ease of communication had the strongest relationship with customer satisfaction when compared to product quality and on-time delivery, which highlights the importance of focusing on proactive and effective communication strategies. Similarities and differences between customer and employee perceptions were observed, and main differences were found to be regarding delivery performance and responsiveness. The results also indicated that due to the operational context of the case company, several factors cannot be influenced by the case company because they are dependent on the supplying factories who produce and deliver the products. The study provided knowledge of the current state at the case company as well as useful recommendations for improving communication processes, delivery monitoring, and coordination with supplying factories. Furthermore, the study contributes to the theory by providing empirical evidence for the positive influence of communication into customer satisfaction. The study also demonstrated that analysing both internal and external perceptions of the performance, an organization can gain a comprehensive overview of their current operational state.

Tuotteen laatu, toimitusvarmuus ja tehokas kommunikointi ovat kriittisiä tekijöitä toimittajan kilpailukyvylle, varsinkin B2B kontekstissa. Toimittajan laatua ja luotettavuutta voidaan arvioida asiakastyytyväisyyden kautta, minkä takia on tärkeää, että yritykset keskittyvät sen ylläpitoon ja kehittämiseen. Asiakastyytyväisyys johtaa myös lojaalisuuteen sekä pitkäaikaisiin suhteisiin asiakkaiden ja toimittajien välillä. Tämän työn tarkoituksena oli arvioida energia-alalla toimivan kohdeyrityksen suorituskykä sekä tunnistaa kehityskohteita asiakastyytyväisyyden ja operatiivisen toiminnan parantamiseksi. Tutkimus toteutettiin yksittäisenä tapaustutkimuksena, jossa käytettiin sekä laadullisia että määrällisiä tutkimusmenetelmiä. Yrityksen sisäisiä näkemyksiä kerättiin puolistrukturoiden haastattelujen avulla, ja ulkoisia havaintoja asiakkailta kerättiin kyselylomakkeen kautta. Kerätylle datalle toteutettiin teemalliset ja tilastolliset analyysit vahvuuksien, heikkouksien sekä kehityskohteiden löytämiseksi. Tutkimuksen tulokset osoittivat, että tuotteen laatu koetaan kohdeyrityksen vahvuutena, kun taas toimitusvarmuutta ja asiakkaiden ongelmiin reagoimista tulisi kehittää. Korrelaatiotestit näyttivät, että kommunikoinnin helppoudella oli suurin yhteys asiakstyytyväisyyteen verrattuna tuotteen laatuun ja toimitusvarmuuteen, mikä korostaa proaktiivisten ja tehokkaiden kommunikointistrategioiden tärkeyttä. Yhtäläisyyksiä ja eroja asiakkaiden sekä työntekijöiden välillä havainnoitiin, ja suurimmat erot liittyivät toimitus- ja reagointikykyihin. Tulokset osoittivat myös, että kohdeyrityksen toimintamallin vuoksi moniin asioihin ei voida suoraan vaikuttaa, koska ne ovat riippuvaisia tehtaista, jotka valmistavat ja toimittavat tuotteet. Tutkimus antoi tietoa kohdeyrityksen nykytilasta sekä hyödyllisiä suosituksia viestintäprosessien, toimitusten seuraamisen, sekä tehtaiden kanssa tapahtuvan kommunikoinnin parantamiseen. Lisäksi, tutkimus tukee olemassa olevaa teoriaa tarjoamalla empiirisiä tuloksia viestinnän tärkeydestä asiakastyytyväisyyteen. Tutkimus osoitti myös, että analysoimalla sekä sisäisiä että ulkoisia havaintoja suorituskyvystä, yritykset voivat saada kattavan kokonaiskuvan nykyisestä toimintatilastaan.
Keywords: customer satisfaction; Industrial Systems Analytics; Master's Programme in Industrial Systems Analytics